Unveiling the Impact of Intrathecal Fibrinolysis on Aneurysmal Subarachnoid Hemorrhage: A Meta-Analysis of Randomized Controlled Trials - Nolan, John; Wijaya, Audrey Rachel; Johansyah, Theodorus Kevin Putra; Krisnawan, Gede Aditya Ersa (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Aneurysmal subarachnoid hemorrhage (aSAH) poses a significant challenge in neurological emergencies, demanding effective therapeutic interventions to improve patient outcomes. Intrathecal fibrinolysis has emerged as a potential intervention to promote the resolution of blood clots within the subarachnoid space. within the subarachnoid space.Extensive literature searches identified relevant RCTs exploring intrathecal fibrinolysis for aSAH management. Data extraction included study characteristics, the quality assessment of the study, and primary outcomes: delayed ischemic neurological deficit (delayed ischemic neurological deficit (DIND)) occurrence and poor neurological recovery (defined by GOS 1–3 or mRS 3–6). Along with the complications and drug preferences.9 RCTs were included in this meta-analysis. The majority of the RCTs demonstrate the promising effect of intrathecal fibrinolysis. Intracisternal fibrinolysis was found to significantly diminish the incidence of delayed ischemic neurological deficit (DIND) (RR, 0.54; 95% CI, 0.32–0.91) and poor neurological recovery (defined by GOS 1–3 or mRS 3–6) events (RR, 0.65; 95% CI, 0.47–0.90). The significant impact in delayed ischemic neurological deficit (DIND) events also showed in the subgroup analysis along with urokinase administration (RR, 0.31; 95% CI, 0.16–0.62). While intraventricular fibrinolysis did not achieve statistical significance for the primary outcomes, overall findings suggested a beneficial effect considering the choice of drugs administered.This comprehensive meta-analysis highlights the potential benefits of intrathecal fibrinolysis in reducing delayed ischemic neurological deficit (DIND) occurrence and improving neurological recovery in aSAH patients. The promising results with intracisternal fibrinolysis and urokinase administration warrant further consideration in treatment protocols. Our findings contribute valuable insights, guiding evidence-based clinical decision-making and promoting advancements in aSAH management.
Keywords: subarachnoid hemorrhage; intracisternal fibrinolysis; intraventricular fibrinolysis; delayed ischemic neurological deficit; plasminogen activators